Palm oil clinker as a novel bio-filler in intumescent fire protective coatings for steel / Siti Aisyah Syaerah Mustapa - Siti Aisyah Syaerah, Mustapa (2018)
Intumescent coatings are an effective method for fire protection of steel structures to ensure the fire safety and prevent the building from collapse in the fire incident. The search for more environmental friendly intumescent coatings has led to the utilization of palm oil clinker (POC) as a novel bio-filler in intumescent coatings in order to improve fire protection performance, mechanical strength and water resistance of steel structures. The purpose of this research is to develop the best composition of intumescent coatings using POC and hybrid fillers. In this research, three flame-retardant additives, i.e. ammonium polyphosphate, pentaerythritol and melamine were mixed with acrylic binder and flame-retardant fillers to produce the intumescent coatings. The first step of this research involved the investigation on the influence of different particle size of POC (micro and nano sizes) as a single filler to the intumescent coatings. The second part of the study attempted to investigate the effect of the optimum percentage of filler in the intumescent coatings formulation. For this part, four specimens using four different percentages of POC were prepared. After that, this research continued with the investigation on the effect of using different hybrid fillers to the intumescent coatings. Then, the last part of research was the investigation on the effect of binders (solvent-borne and water-borne) to the intumescent coatings performance. All specimens were investigated by using the Bunsen burner test, thermogravimetry analysis, field emission scanning electron microscope, static immersion test and adhesion strength test. The surface spread of flame test was carried out on the specimens with the best fire protection performance. It was found that the incorporation of micro size POC as a single filler gives better thermal stability and fire protection performance to the intumescent coatings due to its higher thermal stability. Meanwhile, the addition of 18 wt. % of micro size POC as a single filler in the intumescent coatings was found to be the optimal percentage of filler which resulted in significant improvement in thermal stability as well as the best fire protection performance. For hybrid fillers formulation, the addition of aluminium hydroxide gave better water resistance with the lowest rate of weight change in specimen C2/PTA, while the addition of magnesium hydroxide enhanced the bonding strength of specimen C1/PTM. Also, specimen C3/PTMA with the combination of POC and hybrid fillers showed an excellent fire protection performance with the highest thermal stability, water resistance and mechanical properties. The last part of research showed that the formulation of intumescent coatings with solvent-borne binder led to the best fire resistance performance due to the densest surface structure and greatest expansion. Moreover, the results of the surface spread of flame test showed that all specimens were classified as Class 1, which is the best classification except for specimen B3/20% which is classified as class 2. It can be concluded that the optimum combination of POC and hybrid fillers resulted in intumescent coating with the greatest fire protection performance.